Prosedur Percutaneous Trans Luminal Angioplasty (PTA) Pada Pasien Dengan Kasus Aneurisma Artery Popliteal (AAP) - Muh Reza Mappagau; Putu Adi Susanta (The Journal General Health and Pharmaceutical Sciences Research, 2023)
Popliteal Artery Aneurysm (AAP) is a pathological dilation of the popliteal artery, and although often asymptomatic, can lead to serious complications such as rupture, thrombosis, or embolism. Aneurysms if ruptured can result in internal bleeding such as, stroke, and can sometimes be fatal. This research method is a literature review study, where literature exploration is carried out in various databases with keywords such as Percutaneous Transluminal Angioplasty (PTA)", Popliteal Artery Aneurysm (AAP) cases. Percutaneous transluminal angioplasty (PTA) in popliteal artery aneurysm (AAP) involves patient preparation, tools, procedure, post-operative care, and outcome evaluation. Patient preparation includes education, renal function evaluation, medication adjustment. Equipment preparation includes catheterization table, fluoroscopy system, various types of catheters, appropriate contrast agent. The PTA process includes insertion of the catheter into the femoral artery, evaluation and delineation of the popliteal artery, and completion of the procedure. PTA examination in AAP requires careful preparation and coordinated medical team collaboration to achieve optimal results. Percutaneous transluminal angioplasty (PTA) has proven to be effective as a primary therapeutic option to treat popliteal artery aneurysms (AAP) and prevent popliteal artery stenosis. Risk factors such as advanced age, male gender, and cardiovascular disease were considered in the literature analysis. Although PTA successfully improves the diameter of the popliteal artery as a minimally invasive method, it is important to recognize that the success of the procedure and the decision to use stents have a significant impact on the final outcome.